Marked Decrease in Urgent Listing for Liver Transplantation Over Time: Evolution of Characteristics and Outcomes of Status-1 Liver Transplantation. Issue 1 (January 2018) - Wong, Linda L.; Truong, Hung P.; Seto, Todd; Lacar, Lea; Naugler, Willscott E.
Abstract : Background: Approximately 5% of liver transplants annually are performed urgently with "status-1" designation. This study aims to determine if the demand, characteristics, and outcome for status-1 liver transplantation has changed over time. Methods: We used the Scientific Registry of Transplant Patients (2003-2015) to characterize 2352 adult patients who underwent 2408 status-1 liver transplants and compared them between Era1 (2003-6/2009) and Era2 (7/2009-2015). Results: Overall, there were fewer liver transplants performed with the status-1 designation in Era2 than Era1 (1099 vs 1309). Although the number of urgent liver transplants was relatively constant with successive years, the proportion transplanted with status-1 designation decreased markedly over time. Era2 patients were older (43.2 years vs 41.7 years, P = 0.01) and less likely be ABO-incompatible (1.1% vs 2.4%, P = 0.01) or retransplant (77 vs 124, P = 0.03). In terms of disease etiology, the largest group was "acute liver failure (ALF), nonspecified" (43.4%). There was no difference in proportion with drug-induced liver injury (DILI), but the subset of herbal/dietary supplements increased in Era2 (1.3% vs 0.46%, P = 0.04). Survival was increased in Era2 in the overall cohort and for patients with autoimmune disease ( P < 0.05), despite longer waiting times for this etiology (186 days vs 149 days). DILI or nonspecified ALF had shorter waiting times, and 90% were transplanted within 7 days. Conclusions: Liver transplantation for the most urgent indications (status-1) is decreasing while survival remains excellent. Fewer incidences of ALF are classified as indeterminate, mostly as a result of increasing awareness of autoimmune hepatitis and DILI as causes of the syndrome. Abstract : Based on the Scientific Registry of Transplant Patients (2003-2015), the authors assess changes in demand, characteristics, and outcomes for status-1 liver transplantation over time showing a decrease in these cases as well as lower mean waiting time, fewer ABO-incompatible transplants, together with improved survival. Supplemental digital content is available in the text.